Exploring the Denitrification Proteome of Paracoccus denitrificans PD1222 - Olaya-Abril, Alfonso; Hidalgo-Carrillo, Jesús; Luque-Almagro, Víctor M.; Fuentes-Almagro, Carlos; Urbano, Francisco J.; Moreno-Vivián, Conrado; Richardson, David J.; Roldán, María D. (Frontiers in Microbiology, 2018)
Denitrification is a respiratory process that produces nitrous oxide as an intermediate, which may escape to the atmosphere before its reduction to dinitrogen through the nitrous oxide reductase NosZ. In this work, the denitrification process carried out by Paracoccus denitrificans PD1222 has been explored through a quantitative proteomic analysis. Under anaerobic conditions, with nitrate as sole nitrogen source, the synthesis of all the enzymes involved in denitrification, the respiratory nitrate, nitrite, nitric oxide, and nitrous oxide reductases, was increased. However, the periplasmic and assimilatory nitrate reductases decreased. Synthesis of transporters for alcohols, D-methionine, sulfate and copper, most of the enzymes involved in the tricarboxylic acid cycle, and proteins involved in other metabolic processes like lysine catabolism, fatty acids degradation and acetyl-CoA synthesis, was increased during denitrification in P. denitrificans PD1222. As consequence, an enhanced production of the central metabolite acetyl-CoA was observed. After establishing the key features of the denitrification proteome, its changes by the influence of a competitive electron acceptor, oxygen, or competitive nitrogen source, ammonium, were evaluated.